Testing the Ohlson model modified by operating cash flows in the Damascus Securities Exchange (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of this study is to test The Ohlson model modified by operating cash flow in the Damascus Securities Exchange, by measuring: the relevance-value of accounting information represented by Earnings-per-share, the book value of equity, and operating cash flows. The community of the study consisted of (11) banks listed during the period from 2011 to 2020.The study concluded that: The modified Olson model (earnings per share, book value of equity and operating cash flows) is suitable for interpreting changes in stock prices for banks listed in the Damascus Securities Exchange. It explains (29.7%) of the changes in the dependent variable (stock price). and the value relevance improved after entering the controlling variables (company size, financial leverage, and growth rate per share) on the Ohlson model modified by operating cash flows (company size, financial leverage and growth rate per share), which explains (62.7%) of the changes in the share price of the banks listed in the Damascus Securities Exchange. Thus, the accounting information included in the financial report of the banks listed on the Damascus Securities Exchange(the income statement, the balance sheet and the cash flow statement) reflects information that is appropriate to the value of the investors in the Damascus Securities Exchange.